Patients’ preferences, experiences and expectations with wait time until surgery in gynaecological oncology: a mixed-methods study in two gynaecological oncological centres in the Netherlands - Johanna W M Aarts; Christianne A R Lok; Guus Fons; Anne Knegt; Kim van den Berg (BMJ Open)
Objectives Patient-centredness of care during wait time before surgery can be improved. In this study we aimed to assess (1) patients’ experiences with and preferences regarding wait time before surgery; (2) the impact of wait time on quality of life (QoL) and (3) which factors influence patients’ wait time experience.Design, setting, participants We performed an exploratory sequential mixed-methods study among women with gynaecological cancer in two tertiary hospitals. We conducted semistructured interviews and identified aspects of QoL and factors that influenced wait time acceptability through thematic analysis. We developed a questionnaire from this thematic analysis which was completed by 97 women. Descriptive statistics and univariate and multivariate regression analyses were performed.Results Average ideal wait time was 3.5 weeks (±1.7 weeks), minimum and maximum acceptable wait times were 2.2 and 5.6 weeks. Many patients scored above the threshold of the Hospital Anxiety and Depression Scale for anxiety (48%) or depression (34%), had sleeping problems (56%) or experienced pain (54%). A number of factors were more common in patients who indicated that their wait time had been too long: low education level (OR 7.4, 95% CI 0.5 to 5.0, p=0.007), time to surgery >4 weeks (OR 7.0, 95% CI 0.8 to 4.4, p=0.002) and experienced sleep disturbance (OR 3.27, 95% CI 0.0 to 3.1, p=0.05). If patients expectation of wait time was >4 weeks (OR 0.20, 95% CI −4.0 to −0.5 p=0008) or if patients experienced pain (OR 0.26, 95% CI −3.6 to −0.3, p=0.03), they less frequently indicated that wait time had been too long.Conclusion To improve patient-centredness of care, healthcare providers should aim to reduce wait time to 3–4 weeks and ensure that patients are well informed about the length of wait time and are aware of high levels of anxiety, depression and pain during this time. Future studies should evaluate what interventions can improve QoL during wait time.